Finite element analysis of stress distribution around short and long implants in mandibular overdenture treatment - Yeghaneh Memari; Parisa Fattahi; Amir Fattahi; Solmaz Eskandarion; Vahid Rakhshan (Wolters Kluwer Medknow Publications, 2020)
Background: Optimal stress distribution around implants plays an important role in the success of mandibular overdentures. This study sought to assess the pattern of stress distribution around short (6 mm) and long (10 mm) implants in mandibular two implant-supported overdentures using finite element analysis (FEA). Materials and Methods: In this descriptive and experimental study two implant-supported overdenture models with bar and clip attachment system on an edentulous mandible were used. Two vertical implants were connected by a bar. The implant length was 6 mm (short implant) in the first and 10 mm (long implant) in the second model. Vertical loads (35, 65, and 100 N) were applied bilaterally to the second molar area. In another analysis, vertical loads of 43.3 N and 21.6 N were applied to working and nonworking sides, respectively, at the second molar area. Furthermore, the lateral force (17.5 N) was applied to the canine area of overdenture. The stress distribution pattern around implants was analyzed using FEA. Results: The maximum von Mises stress was 57, 106, and 164 MPa around short implants and 64, 118, and 172 MPa around long implants following the application of 35, 65, and 100 N bilateral forces, respectively. Application of bilateral loads created 87 and 65 MPa stress around working and nonworking short implants, respectively; while these values were reported to be 92 and 76 MPa for long implants at the working and nonworking sides, respectively. Increasing the vertical loads increased the level of stress distributed around the implants; however, no considerable differences were noted between long and short implants for similar forces. Following unequal load application, the stress in the working side bone was more than that in the nonworking side, but no major differences were noted in similar areas around long and short implants. Following lateral load application, the stress distributed in the peri-implant bone at the force side was more than that in the opposite side. In similar areas, no notable differences were observed between long and short implants regarding the maximum stress values. Conclusion: Using implants with different lengths in mandibular overdenture caused no major changes in stress distribution in peri-implant bone; short implants were somehow comparable to long implants.